Pengembangan Media Pembelajaran Geografi berbasis Augmented Reality di SMA Walisongo Semarang - Hulinggi, Mawardi; Suharini, Erni; Sholeh, Muh.; Santoso, Apik Budi; Husain, Fadly (Ideas Publishing, 2024)
Augmented Reality (AR) is the realization of a virtual environment by adding virtual information to the real world physical environment. The aim of this research is to develop learning media based on augmented reality in geography subjects, earth rotation material. The method used for this research is the ADDIE development type and model in creating an augmented reality-based learning environment. As a result of this research, it can be concluded that the learning media based on augmented reality has passed the test by getting a percentage score of 80% by the material validator, then getting a percentage score of 95% by the product expert, and finally the learning validator got a percentage score of 85% so that it can This media can be used in the teaching and learning process in classes with geography as the subject of Earth's rotation.